i-search - Ismail, Nora Asyikin; Mohd Azhar, Mohamad Izzul; Mohd Helmi, Mohd Firdaus (Universiti Teknologi MARA, Kedah, 2017)
The exponential growth of information has become a challenges to most of the people nowadays. Due to this reason, there is a need for everyone to have good information search skills to enables them to search the right information in the right time and the right place. i-search have been developed to assist library users and students especially in higher academic institution on how to perform a good search especially by using OPAC and search engine like Google and Yahoo. i-search will become a one stop center for them to learn everything about searching skills. It will also be equipped with the related images and videos to give a better understanding to the users. i-search will become one stop center for library users and students to improve their search skills. It also will equip them will knowledge and skills to find information at the right time and a right place.